(untitled) (Cuea Journal of Business and Economics, 2025)
Bamboo is a plant that has numerous socio-economic as well as ecological benefits. However, the plant faces an uncertain future mainly due to human activities and climate change. This study thus sought to study agricultural intensification and its implications on bamboo vegetation with focus on the dynamics in Narok North constituency in Narok county, Kenya. Guided by a descriptive survey research design, the study collected primary data from 155 household heads and 13 key informants in the study area. Data from sampled household heads was collected using a questionnaire while data from the key informants was collected using a key informant interview guide. Quantitative data from sampled respondents was analysed using descriptive statistics (percentages, mean and standard deviation) as well as inferential statistics (correlation analysis). The study established that majority of the respondents practiced mixed farming in a bid to utilize the limited land while other farming activities included shifting cultivation, commercial farming, sedentary farming among others. The study also established that the slash and burn agricultural activity posed the greatest risk to bamboo vegetation. Finally, the study concluded that agricultural activities were generally threatening the sustainability of bamboo vegetation in the study area (r=0.534, p<0.05). The study therefore concludes that concerted efforts should be put in place by all stakeholders to ensure that agricultural activities are not expanding at the detriment of bamboo vegetation